Design and development of orbit tracking software for a low cost satellite groundstation - Tye, Woei Cherng. (2009)
This report gives an insight to Satellite Orbit Tracking Software developed by the author. The objective of this project is to design and develop a serverclient system for satellite orbit prediction services. The server-client architecture will be based on a Transmission Control Protocol / Internet Protocol (TCP/IP) environment. At the same time, the system will interface with the EGIS ProfiTracker using RS 232 connection to control the antenna rotor for real-time satellite tracking. The server-client system is implemented using .NET Remoting architecture developed by Microsoft .Net framework. This report aims to discuss the hardware, software and functionalities design of the SOTS system developed. The report will also discuss on the SGP model developed by NORAD for satellite orbit prediction and the .NET Remoting architecture. A walk through of the SOTS GUIs will also be discussed.